Microarray-Based Comparisons of Ion Channel Expression Patterns: Human Keratinocytes to Reprogrammed hiPSCs to Differentiated Neuronal and Cardiac Progeny - Leonhard Linta; Marianne Stockmann; Qiong Lin; André Lechel; Christian Proepper; Tobias M. Boeckers; Alexander Kleger; Stefan Liebau (Hindawi Limited, 2013)
Ion channels are involved in a large variety of cellular processes including stem cell differentiation. Numerous families of ion channels are present in the organism which can be distinguished by means of, for example, ion selectivity, gating mechanism, composition, or cell biological function. To characterize the distinct expression of this group of ion channels we have compared the mRNA expression levels of ion channel genes between human keratinocyte-derived induced pluripotent stem cells (hiPSCs) and their somatic cell source, keratinocytes from plucked human hair. This comparison revealed that 26% of the analyzed probes showed an upregulation of ion channels in hiPSCs while just 6% were downregulated. Additionally, iPSCs express a much higher number of ion channels compared to keratinocytes. Further, to narrow down specificity of ion channel expression in iPS cells we compared their expression patterns with differentiated progeny, namely, neurons and cardiomyocytes derived from iPS cells. To conclude, hiPSCs exhibit a very considerable and diverse ion channel expression pattern. Their detailed analysis could give an insight into their contribution to many cellular processes and even disease mechanisms.